2019
DOI: 10.3390/su11236648
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Knowledge Domain of Smart-City Research: A Bibliometric and Scientometric Analysis

Abstract: As urbanization continues to accelerate, the number of cities and their growing populations have created problems, such as the congestion and noise related to transportation, the pollution from industry, and the difficulty of disposing of garbage. An emerging urban strategy is to make use of digital technologies and big data to help improve the quality of life of urban residents. In the past decade, more and more researchers have studied smart cities, and the number of literature in this field grows rapidly, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 149 publications
(245 reference statements)
0
49
0
1
Order By: Relevance
“…Likewise, the indicators of the collaboration structure, which measure the links between the authors, institutions, and countries, have been analyzed by means of network processing tools and maps due to their reliability and suitability in the bibliometric analysis [88,89].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the indicators of the collaboration structure, which measure the links between the authors, institutions, and countries, have been analyzed by means of network processing tools and maps due to their reliability and suitability in the bibliometric analysis [88,89].…”
Section: Methodsmentioning
confidence: 99%
“…This study on cultured meat was based on the science literature from the Science Citation Index Expanded (SCI-EXPANDED) database of the Web of Science (WoS) Core Collection database from Clarivate Analytics (formerly known as the Institute for Scientific Information). Using WoS as the search source provided researchers with quality literature and gave solid basis to the study (Jacso, 2005;Zhao et al, 2019;Zhu and Liu, 2020). Some comparative studies concluded that WoS and Scopus retrieved no duplicates, while Google Scholar retrieved multiple copies (Adriaanse and Rensleigh, 2013;Driedger and Weimer, 2015).…”
Section: Data Sourcesmentioning
confidence: 99%
“…However, its move towards sustainability suffered from several key issues, covering low community awareness in sustainability values, local context, general geographical factors [11,21], disintegrated management [2,21], and a lack of/and consequently a need for technologies, supporting implementation of accepted sustainability decisions [7,21]. Thus, a smart city concept was actively used during recent decades, especially the last five years [3], demonstrating different and efficient ways of involving digital technologies for more sustainable solutions [22]. The other study [23] reveals new debates on smart cities, focused on the four dichotomies concerning strategic principles that support smart city development: (a) Technology-led; Holistic; (b) Top-down; Bottom-up; (c) Double Helix; Quadruple Helix; and (d) Mono-dimensional; Integrated intervention logic.…”
Section: Complexity and Adaptability In A Collaborative Smart City Modelmentioning
confidence: 99%
“…The smart city idea has been evolving over the last few years, witnessed by a bunch of research devoted to definition analysis of smart city concepts [1][2][3][4][5][6][7]. In their works it is highlighted that, today, a smart city concept is considered both as a theoretical approach (a gradual movement from the focus on IT modernisation of infrastructure in the late 1980s to a holistic approach of city sustainability in two decades) and as practical precedent in different formats [8], indicating those cases already well implemented across the world and in many places with smart city strategies.…”
Section: Introductionmentioning
confidence: 99%